Finite element analysis of the biomechanical behavior of four osseointegrated prosthetic designs - Guo, Zi-Xuan; Wang, Zhen; Zhao, Xue-Lin; Cao, Cheng-Wei; Huang, Zi-Fu; Sun, Zhao-Hang; Zheng, Yu-Shu; Xu, Meng (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveOsseointegration is a critical determinant of the long-term stability and functional performance of orthopedic implants, with prosthetic morphology exerting substantial influence on biomechanical loading and bone–implant interface dynamics. This study aimed to evaluate the biomechanical behavior of four representative osseointegrated prosthetic designs using finite element analysis, to inform clinical application and guide optimization in prosthetic design.MethodsThree-dimensional finite element models were constructed to simulate host bone integrated with four distinct prosthetic configurations: (1) a threaded prosthesis representing the Osseointegrated Prostheses for the Rehabilitation of Amputees system, (2) a smooth press-fit prosthesis simulating the Osseointegrated Prosthetic Limb, (3) a titanium alloy prosthesis with a multi-porous surface, and (4) a molybdenum-rhenium (Mo-Re) alloy prosthesis with a multi-porous surface. Simulated physiological loading conditions were applied to evaluate stress distribution within prosthetic structures, interfacial mechanics at the bone-prosthesis junction, and stress transfer to surrounding osseous tissue.ResultsAll four prosthetic designs exhibited stress concentration at the distal stem region, with peak stress values ranging from 179 to 185 MPa, indicating comparable load-bearing characteristics. Incorporation of a multi-porous surface effectively reduced stress concentration on the inner cortical wall associated with groove geometry. The two multi-porous configurations demonstrated similar load transfer patterns, with maximum stress in adjacent bone tissue recorded at 20.4 MPa. The Mo–Re alloy prosthesis exhibited reduced deformation under equivalent loading due to its higher elastic modulus. Maximum stress within the porous section was 5.3 MPa for the Mo–Re prosthesis and 9.3 MPa for the titanium alloy variant, with no evidence of critical stress accumulation.ConclusionThe multi-porous Mo–Re alloy prosthesis demonstrated favorable mechanical compatibility through the optimized integration of material properties and structural design. Findings from the finite element analysis support its potential utility in osseointegrated orthopedic applications.